Evaluation of the main oral manifestations associated with Down Syndrome: Integrative review (Research, Society and Development, 2021)
Down Syndrome or Trisomy of chromosome 21, as it is also known worldwide, is characterized by an error in chromosome distribution with the presence of an extra chromosome in the distal portion of it, generating specific physical and clinical characteristics throughout these people's lives. This paper aims to identify and discuss the main issues related to the role of oral health in the quality of life of people with Down syndrome. A search for papers was carried out in the following electronic databases: BIREME and PubMed, between the years 2010 to 2020. The search for electronic databases retrieved 22 articles. After reading the title and abstract, reading in full and applying the inclusion and exclusion criteria, a total of 09 articles were selected. It is concluded that there are frequent oral alterations in people with Down syndrome and some of these can be observed and treated from the first months of the child's life. In this way, the present study contributes in a scientific way to the general knowledge of oral problems and frequent alterations in people with down syndrome and elucidates their means of prevention and dental treatments from early childhood as a way to improve the quality of life and well-being of these patients.